CO2 Emissions, Energy Consumption and Economic Growth In Malaysia : A Cointegration Approach - Lim, Jessica Lay See (2017)
This paper investigates the short run and long run relationships between energy consumption, economic growth and carbon emission in Malaysia using annual data from 1982 to 2011. For better understanding of the dynamism, the study first examines the dynamics between energy consumption, economic growth and capital formation. The results indicate that unidirectional causality runs from economic growth to capital formation in the short run. The result also shows that Malaysia is an energy dependent country as evident from the bidirectional causality between economic growth and energy consumption in both the short and long run. The study continues to study the dynamics between energy consumption, economic growth and carbon emissions. With carbon emissions added into the framework, there is evidence of a bidirectional relationship between GDP and EC and EC with CO2. One interesting result to note the existence of a unidirectional relationship running from CO2 and GDP in the long run. With the country’s goal to reduce carbon emissions, reduction in CO2 emission will have an adverse impact on the country’s economic growth. However, the study found that the current recommended policies might mitigated the problem.